1998
DOI: 10.1046/j.1537-2995.1998.38298193099.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinically applicable method for determining the three major alleles at the Duffy (FY) blood group locus using polymerase chain reaction with allele‐specific primers

Abstract: This simple and rapid polymerase chain reaction method was shown to detect the three common alleles at the FY locus in two representative ethnic populations. Its future use as an independent technique in red cell FY investigations and for fetal genotyping in hemolytic disease of the newborn is predicted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 19 publications
4
62
0
5
Order By: Relevance
“…Patient A's sample was typed by serology as Fy (a-b-) which is very rare in Europeans but common in West Africans. 48 Subsequent molecular investigations, using allele-specific primers 49,50 and the blood group genotyping system BLOODchip, 42,51 demonstrated that patient A has the rare FY*0/FY*X genotype which predicts weakened Fy b antigen expression on erythrocytes. This weakened antigen expression, coupled with hemizygosity for the FY*B allele, made serological detection of the Fy b antigen very difficult and could have led to the erroneous interpretation that the Duffy antigen was diminished, as is the case in the 4.1R(-) mouse.…”
Section: Blood Group Antigen Expression On 41r(-) Erythrocytesmentioning
confidence: 99%
“…Patient A's sample was typed by serology as Fy (a-b-) which is very rare in Europeans but common in West Africans. 48 Subsequent molecular investigations, using allele-specific primers 49,50 and the blood group genotyping system BLOODchip, 42,51 demonstrated that patient A has the rare FY*0/FY*X genotype which predicts weakened Fy b antigen expression on erythrocytes. This weakened antigen expression, coupled with hemizygosity for the FY*B allele, made serological detection of the Fy b antigen very difficult and could have led to the erroneous interpretation that the Duffy antigen was diminished, as is the case in the 4.1R(-) mouse.…”
Section: Blood Group Antigen Expression On 41r(-) Erythrocytesmentioning
confidence: 99%
“…El programa de PCR, los oligonucleótidos partidores y la estrategia de amplificación utilizada fueron tomadas de Olsson y cols 41 . Una vez realizada la amplificación, los productos obtenidos se resolvieron en geles de agarosa 1,5 a 2% en buffer TAE, y visualizados a fuente de radiación UV por adición de bromuro de etidio.…”
Section: Rev Méd Chile 2004; 132: 663-672 a R T í C U L O D E I N V Eunclassified
“…El gen FY se ubica en el cromosoma 1, en la posición 1q21-q22 y codifica para una proteína de 338 aminoáci-dos 38 . Este sistema posee dos alelos FYA y FYB con relación de codominancia entre ellos y donde el polimorfismo FYA/FYB radica en una mutación en el nucleótido 131 (G A) que genera un cambio aminoacídico y que otorga la especificidad antigénica exhibida [39][40][41] . Además de éstos, se ha caracterizado otro alelo que presenta frecuencias inusualmente altas denominado FY nulo o silente (FY-) en población de origen negroide.…”
unclassified
“…Because we did not have access to the Fy phenotype in our cohort, we genotyped the c.-67 nucleotide position of the DARC gene by direct sequencing, which is characterized by a T>C substitution at the homozygous state in Fy(a-b-) samples [32]. 31 out of 47 samples (66.0%) were predicted to be Fy(a-b-) (table 2), which is in the range of what reported before (63.0%; χ 2 = 0.12; p = 0.7276) [33] and confirms the African origin of our cohort. Of this subset, 17 were potentially of clinical interest (table 2), which is significantly more than what was observed by Kappler-Gratias et al [30] (6.5% vs. 54.8% in this study; χ 2 = 17.07; p = 0.000036).…”
Section: Resultsmentioning
confidence: 68%